2022
DOI: 10.1039/d2tc00476c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the internal heavy-atom effect on thermally activated delayed fluorescence: application of Arrhenius and Marcus theories for spin–orbit coupling analysis

Abstract: The mechanism of heavy-atom effect on organic blue TADF emitters is investigated using a combined Arrhenius and Marcus theories approach. Basic molecular design principles of such hybrid organic TADF materials are formulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
(63 reference statements)
3
29
0
Order By: Relevance
“…In this context, to understand the reasons of rISC enhancement under finely controlled energy separation of 1 CT and 3 LE states, we have recently developed a rotationally and vibronically assisted SOC model which explains TADF in a DMAC-TRZ emitter and its derivatives as a result of direct 3 CT- 1 CT twostate model. [20,21] Since TADF materials exhibit emission through the ICT mechanism, the emission wavelength could be systematically tuned through control of ICT state by different combination of D and A units. [22,23] The design of most demanded fast-rISC deep-blue emitters is highly challenging, because the molecular systems with such higher energies of CT states exhibit slower rISC and worse OLED performance.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, to understand the reasons of rISC enhancement under finely controlled energy separation of 1 CT and 3 LE states, we have recently developed a rotationally and vibronically assisted SOC model which explains TADF in a DMAC-TRZ emitter and its derivatives as a result of direct 3 CT- 1 CT twostate model. [20,21] Since TADF materials exhibit emission through the ICT mechanism, the emission wavelength could be systematically tuned through control of ICT state by different combination of D and A units. [22,23] The design of most demanded fast-rISC deep-blue emitters is highly challenging, because the molecular systems with such higher energies of CT states exhibit slower rISC and worse OLED performance.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain statistically weighted values of f 1CT-S0 and k 3CT-1CT , the respective values of all rotamers were added taking into account the contribution of each rotamer provided by relative energies of rotamers and Boltzmann distribution law (S2) (ESI†). As was reported previously, in donor–acceptor type TADF emitters including their HA-derivatives, the rotational 30 and vibrational 23 isomerism has key importance for efficient rISC via the 3 CT→ 1 CT pathway.…”
Section: Resultsmentioning
confidence: 58%
“…Radiative rate constants k r and (reverse) intersystem crossing rates k (r)ISC were calculated using procedures described in detail previously and in Section S4 (ESI†). 23…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter promotes spin-orbit coupling (SOC) between singlet and triplet states, thus facilitating intersystem crossing (ISC) between them, which relaxes the spin ‘forbidden’ radiative transitions [ 12 ]. In general, the heavier the metal atom of a coordination compound, the stronger the SOC [ 13 , 14 , 15 ]. However, recent studies revealed that the presence of heavy atoms does not guarantee efficient ISC, while the nature of ligands may play a critical role in determining the radiation pathway [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%